Prevalence, virulence genes, and antimicrobial profiles of Escherichia coli O157:H7 isolated from healthy cattle in Tunisia - Ghassan Tayh; Salma Mariem Boubaker; Rym Ben Khedher; Mounir Jbeli; Faten Ben Chehida; Aymen Mamlouk; Monia Dâaloul-Jedidi; Lilia Messadi (Journal of Infection in Developing Countries)
Introduction: Shiga toxin-producing Escherichia coli (STEC) O157:H7 is associated with intestinal infection in humans and is considered an important cause of food-borne diseases. The aim of the study was to assess the incidence of E. coli O157:H7 in fecal samples of healthy cattle collected in slaughterhouses (n = 160) and from five farms (n = 100).